Adoptive projects: constructions under evaluation (Papeles, 2022)
This paper aims to reflect theoretically on the exercise of evaluation of adoptive projects and the actions that it entails, a task in which we find ourselves professionally performing for more than 10 years. The article recovers the main keys that direct and organize our intervention in the Registry of Applicants for Guardianship for Adoptive Purposes of the Province of Santa Fe, building the theoretical mediations that serve as a foundation for professional practice, relating them with the general process. Being able to go through this instance of reflection and elucidation of the theoretical, methodological, operational, instrumental aspects defines our ethical position related to this practice (the evaluation of adoptive projects) in relation to the construction of the Institution of Adoption as a Social Issue.
Keywords: adoption; interdiscipline; evaluation; adoptive projects; social issue